2019
DOI: 10.1101/687434
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Toxin Antitoxin MazEF DrivesStaphylococcus aureusChronic Infection

Abstract: 48Staphylococcus aureus is the major organism responsible for surgical implant infections. 49Antimicrobial treatment of these infections often fails leading to expensive surgical intervention 50and increased risk of mortality to the patient. The challenge in treating these infections is 51 associated with the high tolerance of S. aureus biofilm to antibiotics. MazEF, a toxin-antitoxin 52 system, is thought to be an important regulator of this phenotype, but its physiological function 53 in S. aureus is controv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Several studies have reported the essential roles of the type II TA pairs such as VapBC, MazEF, and RelBE in bacterial pathogenesis. 10,11,16 Moreover, HigA plays a vital role in biofilm formation, iron uptake, and carbon metabolism in P. aeruginosa. 14,15,17 Therefore, we investigated the contributions of higA in P. aeruginosa infection by comparing the virulence of the WT, ΔhigA, and higB deletion (ΔhigB) strains in a Galleria mellonella infection model.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported the essential roles of the type II TA pairs such as VapBC, MazEF, and RelBE in bacterial pathogenesis. 10,11,16 Moreover, HigA plays a vital role in biofilm formation, iron uptake, and carbon metabolism in P. aeruginosa. 14,15,17 Therefore, we investigated the contributions of higA in P. aeruginosa infection by comparing the virulence of the WT, ΔhigA, and higB deletion (ΔhigB) strains in a Galleria mellonella infection model.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Several studies have reported the essential roles of the type II TA pairs such as VapBC, MazEF, and RelBE in bacterial pathogenesis. ,, Moreover, HigA plays a vital role in biofilm formation, iron uptake, and carbon metabolism in P. aeruginosa .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation